Comparisons of Characteristics Between Psychological Support Hotline Callers With and Without COVID-19 Related Psychological Problems in China - Zhao, Liting; Li, Ziyang; Tong, Yongsheng; Wu, Mengjie; Wang, Cuiling; Wang, Yuehua; Liu, Nancy H. (Frontiers in Psychiatry, 2021)
Background: To compare the characteristics between hotline callers with and without the Coronavirus Disease 2019 (COVID-19) related psychological problems. Methods: From January 25 to March 31, 2020, 581 callers with COVID-19 related psychological problems (COVID-19 callers) and 695 callers without COVID-19 related psychological problems (non-COVID-19 callers) to the Beijing Psychological Support Hotline were recruited. The demographic characteristics, primary concerns, suicidal ideation, depression and other psychological problems were compared between the two groups of callers. Results: Both groups of the callers were predominantly female and highly educated. The primary concerns reported by the COVID-19 callers were depression (38.4%) and family relationship problems (26.0%). As compared to the non-COVID-19 callers, COVID-19 callers reported more financial (7.4%) and work related problems (4.1%), but revealed lower prevalence of suicidal ideation (47.9% v 71.3%), lower degrees of psychological distress (74.3 v 79.1), intensity of suicidal ideation (0 v 50), severity of depression (57.9 v 65.1), and higher degree of hopefulness (41.1 v 33.6) (all p values < 0.01). Additionally, a lower proportion of COVID-19 callers met the criteria of depressed mood (51.6% v 61.4%) and other 4 symptoms than the non-COVID-19 callers (p values < 0.01). Conclusions: Based on the content of the primary concerns and the relatively low level of depression of the COVID-19 callers, the psychological intervention for them during the pandemic should focus on “psychological supports.” Coping strategies for daily life stressors and promotion of scientific knowledge about the pandemic should also be included in the hotline-related interventions.